The mental health of working women after the COVID-19 pandemic: an assessment of the effect of the rise in sexual harassment during the pandemic on the mental health of Pakistani women using DASS-21 - Akbar, Shehzeen; Ghazal, Pasha (Frontiers in Psychiatry, 2023)
Sexual harassment is one of the major factors accounting for the mental health deterioration of women who leave their homes frequently for work and study. In the after math of COVID-19 pandemic, rise in sexual violence against women is being consistently reported around the globe. In this study we evaluated that whether working women and students aged 18-55 experienced a rise in sexual harassment in the 18 months after lifting of COVID-19 lockdowns in Pakistan. Secondly, using the well-validated psychometric test, DASS-21, we evaluated the psychiatric outcome of this change on the mental health of those women.Methodology: A total of 303 women participated in this study. Personal interviews through a specifically designed questionnaire and DASS-21 were administered to assess the mental health state of participants. The mean age of the participants was 37± 2.8. The study population was further categorised into two main groups of limited and frequent interaction, based on varying levels of frequency of leaving home and interactions with male strangers in their daily routine. Data were analysed and the correlation between limited/frequent interaction and DASS-21 total scores and sub-scores of depression, anxiety and stress, and sociodemographic variables were evaluated using Chi-square test, whereas psychosocial predictors of mental distress were evaluated using multiple linear regression analysis after matching limited and frequent interaction groups using a 1:1 propensity score-matched pair method for sociodemographic covariates.Results: Overall, around 50% of our study population experienced changes in the behavior of male strangers that could be categorised as harassment in their daily life interactions, whereas, 33.66% of participants experienced relatively more sexual harassment post-pandemic than before it. This observation was significantly correlated with the frequency of male interaction, (χ2=5.71, p<0.01).Overall, 34% of our study population scored >60 on the DASS21-total score, whereas 29.04% scored >21 on the depression scale. Moreover, out of all the factors analysed, the extent of interaction with male strangers, increased fear of crimes, and self-perceived increase in mental distress post-pandemic were found to be highly statistically significant predictors of mental distress for all total DASS 21 and sub-scales .In Pakistan, women experienced a rise in sexual harassment cases post-COVID-19.